Determinación de coccidiosis por Eimeria en el ganado bovino que se faena en el camal municipal de la ciudad de Babahoyo - Carmona Ramos, Luciana Lisbeth (2025)
In cattle production, coccidiosis caused by Eimeria represents a considerable challenge, as it causes significant economic losses. This parasitic infection affects both symptomatic and asymptomatic animals, increasing production costs. Therefore, it is considered one of the most significant infectious diseases in cattle farming. For this reason, the main objective of this study was to diagnose coccidiosis caused by Eimeria in cattle, which was carried out in the municipal slaughterhouse of the Babahoyo canton, province of Los Ríos, where we evaluated the incidence of the parasite, with the aim of microscopically identifying the Eimeria parasite with the simple Willis-Molloy flotation technique with a supersaturated sodium chloride solution, by collecting feces directly from the animal's rectum, where samples were taken from 150 cattle due to which research work was carried out between the months of December 2024 and January 2025 in which the breed, sex, age, origin and the methodology used in data processing was the non-parametric statistical design (Chi Square), the methods were inductive-deductive, experimental-descriptive according to the studies carried out through the daily collection of feces, it is concluded that there is no incidence of Eimeria since all the cattle examined in the cases were negative